A coordenação híbrida e a percepção dos fornecedores de manufatura contratada sobre a complementariedade contratual na produção de bens eletrônicos de consumo no estado de São Paulo - Cruz, Valcir de Jesus Sousa da (2014)
In the electronics industry the companies owners of brands ( OEM ) are hiring outside manufacturing service providers ( EMS ) , and transfer to them major portions of their production. The EMSs have contributed to the OEMs in activities such as supply of components, engineering, manufacturing and distribution services. With the growth of this practice, the EMSs accumulate ever more capacity as providers of highly specialized commoditized electronic products, reducing costs and sharing risks across the electronic industry.The objective of this research was to scale the perception among EMSs, about the attributes of trust, mutuality and leadership, governance mechanisms as complementary to contract manufacturing in the consumer electronics industry considering the contributions of Ménard (2004) for the development of hybrid modes of governance. A field survey was carried out, being interviewed companies providing contract manufacturing headquartered in São Paulo. The analyzes show that allowed transactions providing electronic manufacturing are coordinated by complementary mechanisms to contracts through a governance model multiple hybrid formed by trust, mutuality and leadership.